Formulating a single thioether-bridged oleate prodrug into a self-nanoemulsifying drug delivery system to facilitate oral absorption of docetaxel. (14th January 2019) - Cui, Weiping; Zhang, Shenwu; Zhao, Hanqing; Luo, Cong; Sun, Bingjun; Li, Zhenbao; Sun, Mengchi; Ye, Qing; Sun, Jin; He, Zhonggui
Abstract : Single thioether-bridged oleate prodrug (DTX-S-OA) efficiently incorporated into SNEDDS can avoid P-gp efflux, facilitate lymphatic transport and thus improve bioavailability. Abstract : Oral chemotherapy of docetaxel (DTX) is restricted by active P-glycoprotein (P-gp) efflux, hepatic first-pass metabolism and then poor oral absorption. Herein, a lipophilic thioether-bridged oleate prodrug (DTX-S-OA) and an ester-bond linked oleate prodrug of docetaxel (DTX-OA) were synthesized and efficiently incorporated into a self-nanoemulsifying drug delivery system (SNEDDS) using core-matching technology with a high drug-loading rate. DTX-S-OA SNEDDS produced a uniform droplet size of about 30 nm and a significantly high drug loading capability (60 mg mL −1 ), compared with DTX SNEDDS (20 mg mL −1 ). Additionally, DTX-S-OA SNEDDS exhibited a markedly slower drug release property and higher (>2-fold) drug solubilization in the aqueous phase after 60 min lipolysis compared with DTX SNEDDS. In situ single-pass intestinal perfusion and intestinal biodistribution studies demonstrated that the membrane permeability and intestinal bioadhesion of SNEDDS were significantly increased. Moreover, DTX-S-OA showed a comparable ability with verapamil in inhibiting P-gp efflux. Lymphatic transport studies confirmed that DTX-S-OA SNEDDS could significantly enhance intestinal lymphatic transport. Notably, the bioavailability of DTX-S-OA SNEDDS was 6.2-fold and 2.0-fold higher than that of the DTX solution and DTX SNEDDS, respectively. Furthermore, DTX-S-OA achieved a more rapid release of free DTX from the prodrug in systemic circulation than DTX-OA. Therefore, such a unique combination strategy of the single thioether-bridged DTX-oleate prodrug and SNEDDS is a promising platform to enable effective oral delivery of DTX.